Pengembangan Aplikasi Sistem Pakar Berbasis Web untuk Analisis Penyakit Tanaman Cabai dengan Model Forward Chaining - Ilahi, Rafi Kurnia; Samala, Agariadne Dwinggo (TSAQOFAH, 2025)
Expert systems are a branch of artificial intelligence designed to replicate the reasoning abilities of a human expert in solving specific problems within a particular domain. This study aims to develop a web-based expert system using the forward chaining model to analyze and diagnose diseases in chili plants. The system is built using a rule-based approach, where users select observed symptoms and the system automatically generates a diagnosis through forward reasoning. Testing was conducted through black-box testing to ensure all features functioned as expected, and accuracy testing was performed by experts using ten real case studies. The results showed that the system successfully provided accurate diagnoses for all cases, achieving an accuracy rate of 100%. These findings demonstrate that the developed expert system is effective as a knowledge-based diagnostic tool. Furthermore, the system holds significant potential for expansion to other problem areas through adjustments to its knowledge base.